1987
DOI: 10.1111/j.1751-1097.1987.tb04870.x
|View full text |Cite
|
Sign up to set email alerts
|

SKIN PHOTOSENSITIVITY: DURATION and INTENSITY FOLLOWING INTRAVENOUS HEMATOPORPHYRIN DERIVATES, HpD and DHE

Abstract: In this pilot study, the duration and degree of skin photosensitivity after intravenous injection of HpD or DHE was tested sequentially once a week, using a solar simulator delivering 19.5 ± 1.5 J cm−2 to an area of skin 1.4 cm diameter. The longest duration of skin photosensitivity was 7 weeks amongst the 12 patients studied. In 180 other patients, the incidence of sunburn following PDT was less than 10% over a period of 7 y. Sunburn was always minimal (mild redness and swelling–no blisters), and required no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
3

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 6 publications
0
27
0
3
Order By: Relevance
“…by the following mechanism. In a first step, the O 2 Several factors could explain the decrease of the cell produced forms a complex with DMPO (Eq. (11)), the survival when liposomes are used as drug carriers.…”
Section: Efficiency Of Bca In Dmpc Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…by the following mechanism. In a first step, the O 2 Several factors could explain the decrease of the cell produced forms a complex with DMPO (Eq. (11)), the survival when liposomes are used as drug carriers.…”
Section: Efficiency Of Bca In Dmpc Liposomesmentioning
confidence: 99%
“…In PB, Beems et al its physical and chemical properties: PII has a low molar showed that, upon illumination, BCA was able to induce absorption coefficient above 600 nm, where the skin oxygen consumption. The use of specific quenchers em-1 penetration of light is optimal, and induces long lasting phasized the presence of singlet oxygen ( O ) in the 2 skin photosensitivity [2]. reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely studied photosensitiser is Photofrin which until recently, was the only photosensitiser approved for clinical use. Photofrin, though a potent photosensitiser, causes prolonged cutaneous photosensitivity (Razum et al, 1987) and offers limited tumour selectivity (Agrez et al, 1983;Gomer & Dougherty, 1979). We have recently reported on the photosensitisation kinetics produced by systemic administration of another agent, 5-aminolaevulinic acid (ALA) Loh et al, 1992 (Loh et al, 1992).…”
mentioning
confidence: 99%
“…Although HpD has tumour-localising properties with a discnrmination towards normal tissue of about 2-3:1 for various malignant lesions, several factors limit its widespread use as a photodiagnostic agent, including the heterogeneous chemical composition and the presence of non-fluorescent aggregated material, the limited selectivity and the prolonged persistence of general cutaneous photosensitivity if administered in therapeutic doses (Dougherty, 1987;Razum et al, 1987). The development of new sensitisers has mainly emphasised their therapeutic effects, including high single oxygen yield for the induction of tumour necrosis and light absorption at wavelengths close to 700nm for deep light penetration.…”
mentioning
confidence: 99%